Analisis Risiko Kesehatan Lingkungan Pajanan PM10 Pada Karyawan Operator Di Spbu Lapadde Km 3 Kota Parepare - Indah Asmita Dewi; Rahmi Amir; Makhrajani Majid (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2022)
PM10 is a dust with solid and liquid particulates floating in the air with a media value of 10 microns in aerodynamic diameter. This particulate matter (PM10) can enter through the nose and throat and can reach the lungs. This inhaled particulate metter has a negative impact on health problems, especially on the lungs and heart organs. The purpose of this study is to determine the estimated risk level of PM10 exposure to gas station operator employees. The research method used in this study is the Environmental Health Risk Analysis (ARKL) method. and carried out in July 2021 with a sample of 8 employees of gas station operators. The total concentration of PM10 in ambient air is 0.020 mg/m3 which is carried out at the location point, namely the refueling area at the gas station. The results of the calculation of the Realtime and Lifetime RQ values ​​are obtained 1, the risk for SPBU Operator Employees can still be said to be safe at the gas station for 8 hours per day for the next 30 years.